Initial characterization of stiff skin‐like syndrome in West Highland white terriers. Issue 3 (June 2016) - Doelle, Maren; Linder, Keith E.; Boche, Janna; Jagannathan, Vidhya; Leeb, Tosso; Linek, Monika
Abstract : Background: Stiff skin syndrome and systemic or localized scleroderma are cutaneous disorders characterized by dermal fibrosis and present clinically with induration of the skin, with or without joint, internal organ or vascular involvement. Objectives: To provide clinical, histological and preliminary genetic analysis of two West Highland white terrier siblings presenting with indurated skin resembling stiff skin syndrome in humans. Animals: Two client owned full sibling West Highland white terriers from two different litters. Methods: Clinical examination, histopathological examination and whole genome sequencing analysis of affected and unaffected West Highland white terriers. Results: Affected dogs exhibited markedly indurated skin that was attached firmly to the underlying tissue and incomplete closure of the mouth and eyes. No abnormalities were found by neurological or orthopaedic examination, radiographs of the head or whole body computed tomography. Histologically, the dermis and pannicular septa were thickened by a marked increase in coarse collagen fibres and a mild to moderate increase in collagen fibre diameter. The syndrome most likely follows an autosomal recessive mode of inheritance. The sequence analysis did not reveal any obvious causative variant in the investigated candidate genes ADAMTSL2 and FBN1 . Conclusion and clinical importance: The clinical phenotype and histopathological features of two West Highland white terrier siblings resembled stiff skin syndrome in humans. Unlike in humans, or previously described beagles with stiff skin, there was no restriction of joint mobility. Genetic analysis did not detect a candidate causative variant and warrants further research. Abstract : Background ‐ Stiff skin syndrome and systemic or localized scleroderma are cutaneous disorders characterized by dermal fibrosis and present clinically with induration of the skin, with or without joint, internal organ or vascular involvement.Objectives ‐ To provide clinical, histological and preliminary genetic analysis of two West Highland white terrier siblings presenting with indurated skin resembling stiff skin syndrome in humans.Conclusion and clinical importance ‐ The clinical phenotype and histopathological features of two West Highland white terrier siblings resembled stiff skin syndrome in humans. Unlike in humans, or previously described beagles with stiff skin, there was no restriction of joint mobility. Genetic analysis did not detect a candidate causative variant and warrants further research.